Liberia, Ebola and the pitfalls of state-building: Reimagining domestic and diasporic public authority - Pailey, R (Oxford University Press, 2017)
Using the Ebola outbreak of 2014/2015 in Liberia as a case study, this article demonstrates that by converting ‘private activities and resources’ for public health service delivery, Liberian domestic and diasporic non-government actors effectively broadcasted public authority at meso- and micro-levels previously assumed to be the exclusive domain of government and international institutions. Moving beyond the structural violence and state-building frameworks, I argue that while Liberia's pursuit of a vertical state-building agenda at the behest of international donors unravelled during Ebola, the public health measures employed by non-government Liberian actors were constituted by horizontal nation-building objectives. This refashioned how we think about public authority in post-war states and beyond. The article provides a systematic documentation of how and why Liberians ‘inside’ and ‘outside’ the geographic territory of the post-war state used their individual and collective agency to eradicate Ebola, and why their interventions are important for a larger discussion about the trajectory of post-Ebola recovery. Though it is difficult to prove a causal relationship between the interventions of non-government Liberian actors and the gradual decline in Ebola incidence rates, I underscore important correlations between their public health measures and Ebola eradication.